THE EFFECT OF UNEMPLOYMENT, ECONOMIC GROWTH AND HUMAN DEVELOPMENT INDEX ON POVERTY LEVELS IN SUMBAWA REGENCY IN 2012-2021 - Edi Irawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of the unemployment rate, the rate of economic growth and the human development index on the poverty rate in Sumbawa Regency for the period 2012 – 2021. The research method used in this study is a quantitative method by using secondary data that is time-series data, namely in 2012 – 2021 sourced from the Central Statistics Agency for Sumbawa Regency. Analysis of the data used is the multiple linear regression method. The results of the study show that only the unemployment rate and the Human Development Index have a significant effect on the poverty level in Sumbawa Regency during 2012-2021. This is due to several things, including the local government of Sumbawa Regency for less than 10 years launching an increase in human capital development with the hope of reducing poverty by investing in education and health. Because these two investments have been more meaningful for the poor in Sumbawa Regency for the last 10 years. With the realization of this, it will greatly help increase productivity and in turn increase income for the people of Sumbawa Regency